Application of the computing environment maple to the calculation of the dynamics of the electromagnets in the complicated systems of forced control - Baida, E.I.; Clemens, M.; Klymenko, B.V.; Korol, O.G.; Pustovoitov, P.Ye. (Електротехніка і електромеханіка, 2019)
The authors propose a technique for calculating the dynamics of electromagnets operating in complex forced systems. Such forced electromagnets are widely used in electromechanical switching devices, in particular in vacuum contactors, to reduce their size, energy consumption and to increase speed, which indicates the relevance of this topic. A mathematical model of the dynamics of a forced electromagnetic system, which takes into account the peculiarities of behavior in transients of its individual elements – the mechanical system, the magnetic and electrical circuits, taking into account the interaction of the electromagnet with a control device when the apparatus is activated, contains certain signs of scientific novelty and is the purpose of the paper.